The extracellular serine protease from Staphylococcus epidermidis elicits a type 2-biased immune response in atopic dermatitis patients - Abdurrahman, Goran; Pospich, Rebecca; Steil, Leif; Gesell Salazar, Manuela; Izquierdo González, Juan José; Normann, Nicole; Mrochen, Daniel; Scharf, Christian; Völker, Uwe; Werfel, Thomas; Bröker, Barbara M.; Roesner, Lennart M.; et al. (Frontiers in Immunology, 2024)
Background Atopic dermatitis (AD) is a chronic, relapsing inflammatory skin disease with skin barrier defects and a misdirected type 2 immune response against harmless antigens. The skin microbiome in AD is characterized by a reduction in microbial diversity with a dominance of staphylococci, including Staphylococcus epidermidis (S. epidermidis). Objective To assess whether S. epidermidis antigens play a role in AD, we screened for candidate allergens and studied the T cell and humoral immune response against the extracellular serine protease (Esp). Methods To identify candidate allergens, we analyzed the binding of human serum IgG4, as a surrogate of IgE, to S. epidermidis extracellular proteins using 2-dimensional immunoblotting and mass spectrometry. We then measured serum IgE and IgG1 binding to recombinant Esp by ELISA in healthy and AD individuals. We also stimulated T cells from AD patients and control subjects with Esp and measured the secreted cytokines. Finally, we analyzed the proteolytic activity of Esp against IL-33 and determined the cleavage sites by mass spectrometry. Results We identified Esp as the dominant candidate allergen of S. epidermidis. Esp-specific IgE was present in human serum; AD patients had higher concentrations than controls. T cells reacting to Esp were detectable in both AD patients and healthy controls. The T cell response in healthy adults was characterized by IL-17, IL-22, IFN-γ, and IL-10, whereas the AD patients’ T cells lacked IL-17 production and released only low amounts of IL-22, IFN-γ, and IL-10. In contrast, Th2 cytokine release was higher in T cells from AD patients than from healthy controls. Mature Esp cleaved and activated the alarmin IL-33. Conclusion The extracellular serine protease Esp of S. epidermidis can activate IL-33. As an antigen, Esp elicits a type 2-biased antibody and T cell response in AD patients. This suggests that S. epidermidis can aggravate AD through the allergenic properties of Esp.